EVT474: Atmospheric Chemistry / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
This is an undergraduate course oriented to provide undergraduate students with the knowledge and skills for understanding and investigating the phenomenon of air pollution. The course covers the chemistry and dynamic of air pollutants, the sources as well as wide-ranging effects including effects on our bodies and the environment, fate and transport of air pollutants, the legislative framework for air pollution control strategies, air pollution meteorology and atmospheric dispersion modeling. A brief introduction of internal and government regulations related to air pollution problems will be explained. Any current air pollution issues will also be discussed in this course, from its sources to control and mitigation measures.